Innovating art, design, and tourism: a comparative journey of economic empowerment in Malaysia and France - Mohamad Zahari, Nur Azlina (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s global economy, the integration of art, design, and tourism is driving economic growth, as countries leverage creative industries to attract tourists and boost local economies. France has long led in art, fashion, and design, while Malaysia is developing its own creative identity to enhance its tourism sector. By examining strategies from both nations, valuable insights emerge for Malaysia to strengthen its creative economy and appeal to a wider international audience.